Perfil e mapeamento dos acidentes de trânsito fatais com óbito no local, na unidade Francisco Beltrão/PR entre 2010 e 2020 - Leal, Vicente de Albuquerque Maranhão (2023)
Annually in Brazil, more than 1 million accidents are registered, killing about 40 thousand people and leaving more than 370 thousand injured, impacting the economy and thousands of families, according to the Ministry of Health. , the increase in the number of vehicles and alcohol intake are factors that contribute to the high rate of traffic accidents in Brazil. The changes in the 1998 Traffic Code, improving vehicle safety and increasing electronic inspection, did not cause accidents to show a significant reduction, placing Brazil as one of the countries with the most deaths in traffic in the world. an epidemiological, cross-sectional, descriptive, analytical and retrospective study at the Francisco Beltrão Unit (marked by the Scientific Police of Paraná), in the period 2010-2020. of the accident victim and the most dangerous routes that led to bodily injury and fatal outcome, characterized as extremely serious trauma, represented by a total of 726 occurrences with deaths on the spot representing 54% of all fatal occurrences in traffic based on information from medical records in the IML (Institute of Legal Medicine) and the Institute of Criminalistics of Francisco Beltrão / PR. The identifying profile considers: age, sex, and day of the week, precise location of the accident, cause of death by autopsy, presence of ethyl alcohol by blood test, type of vehicle involved and location inside the vehicle, involving cars, trucks, buses, motorcycles, drivers, passengers and pedestrians. The data will be inserted into cartographic maps of highways in the region, identifying the most vulnerable stretches. The information obtained shows that men, adults and young people have the highest number of cases and in line with the leading cause of death in the world among people aged between 15 and 29 years, responsible for taking the lives of 1.24 million people in 182 countries, in 2020. This work aims to establish a profile of the Francisco Beltrão region with the characterization of traffic accidents, which can contribute to its understanding and planning of policies and interventions in traffic safety on highways by adopting measures to mitigate accidents.